INTERAKSI SOSIAL MAHASISWI PENGHUNI ASRAMA MANDAH PUTRI DI KELURAHAN LABUH BARU TIMUR KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - ', Hamidah; ', Resdati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research, which was conducted in Labuh Baru Timur Subdistrict, Payung Sekaki District, Pekanbaru City, aims to find out how the Social Interaction of Female Students Living in the Mandah Putri Dormitory in Sukajadi is as well as the obstacles experienced by female students while living in the Mandah Putri Sukajadi Dormitory. The method used in this research is a descriptive qualitative method. This research uses a purposive sampling technique by taking 6 eight research subjects. Data collection here uses interview, observation and documentation techniques. The data analysis techniques used in this research are data reduction, data presentation, and the stage of drawing conclusions. The theory used in this research is Gillin and Gillin Social Interaction. The result of this research is the Social Interaction of Students at the Mandah Putri Sukajadi Dormitory. able to work together well even if there are slight differences of opinion, but despite this lack of cooperation, they are able to interact well socially and remain well maintained and do not cause problems that hinder their daily routines. Social interaction between female students at the Mandah Putri Dormitory is group social interaction and is associative in nature. Group social interaction between dormitory students means that cooperation is not well established. Keywords: Social Interaction of Mandah Women's Dormitory Students